2017
DOI: 10.1097/md.0000000000005801
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the i-gel and other supraglottic airways in adult manikin studies

Abstract: Background:The i-gel has a gel-like cuff composed of thermoplastic elastomer that does not require cuff inflation. As the elimination of cuff inflation may shorten insertion time, the i-gel might be a useful tool in emergency situations requiring prompt airway care. This systematic review and meta-analysis of previous adult manikin studies for inexperienced personnel was performed to compare the i-gel with other supraglottic airways.Methods:We searched PubMed, the Cochrane Library, and EMBASE for eligible rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
1
9
1
Order By: Relevance
“…17 In the present study, most of the patients in LMA group (60%) had MPC grade II for air way maintenance, however, in i-gel group majority of patients (60%) had MPC grade I for airway maintenance (p=0.60). An et al 18 and Kapoor et al 19 reported findings contrasting to our study. They reported majority of patients with MPC I for airway maintenance in i-gel group as compared to LMA group.…”
Section: Discussioncontrasting
confidence: 99%
“…17 In the present study, most of the patients in LMA group (60%) had MPC grade II for air way maintenance, however, in i-gel group majority of patients (60%) had MPC grade I for airway maintenance (p=0.60). An et al 18 and Kapoor et al 19 reported findings contrasting to our study. They reported majority of patients with MPC I for airway maintenance in i-gel group as compared to LMA group.…”
Section: Discussioncontrasting
confidence: 99%
“…The incidence of failure, unrecognized esophageal intubation, and dislodgement of endotracheal tube are also high. [ 1 22 23 ] A number of studies have been conducted in manikins[ 24 25 26 ] as well as in patients[ 6 7 27 ] using various available SADs. Most authors reported better results with I-gel than with other SADs[ 6 7 8 24 27 ] except LMA supreme.…”
Section: Discussionmentioning
confidence: 99%
“…The success rate under physiologic conditions with ET was comparable to other studies [ 4 , 16 ]. With the SADs, success rates tend to differ largely, depending on the model and the setup [ 2 , 19 ]. AirQ, AuraG, and LT were inserted the fastest in physiologic conditions and CS, most likely because these are easiest to handle.…”
Section: Discussionmentioning
confidence: 99%